EFEKTIFITAS FUNGSI PARLEMEN DEWAN PERWAKILAN DAERAH DALAM MEWAKILI ASPIRASI MASYARAKAT DAERAH MALUKU - Dayanto dan; Asma Karim (IAIN Ambon, 2017)
This research aims to analyze the parliament functions effectiveness of Regional Representative Council in representing the regional community aspirations of Maluku and the factors that influence it. The results of research showed that implementation of parliament functions of DPD RI is not effective due to: (a) the design of DPD RI formal-constitutional authority that tends putting the existence of DPD RI parliament functions which subordinate in relation to DPR RI as chamber system in Indonesian parliament; (b) insufficient ability of DPD RI member as Representative of Maluku in fighting for the community aspirations of Maluku to be product of institutional decision of DPD RI; (c) has not been formulated the strategic planning document of DPD RI Representative of Maluku in accordance with the membership period to become the performance basis for implementing the parliament functions; and (d) has not been functioning the supporting system in form of the representative offices of DPD RI as “aspiration home” for the local community of Maluku which caused an impermanent office facilities. Key words: Function parliament, DPD, aspirations of local communities